Sensory quality, favorability, and antioxidant activity of red bean mochi with addition of skin flour and red dragon fruit flour - Nesza Ayu Mulan; Nunung Cipta Dainy (Sarana Ilmu Indonesia (salnesia), 2025)
Deteriorating environmental conditions in urban areas cause the body to be continuously exposed to free radical compounds. Dragon fruit contains high antioxidants that have potential as anti-free radicals. This research aimed to determine the effect of red bean mochi formulation on sensory characteristics of mochi, nutritional content test and antioxidant activity analysis on red bean mochi with the addition of skin flour and red dragon fruit flour. This study used a completely randomized design (CRD) with four treatment ratios of glutinous rice flour to dragon fruit peel and fruit flour (30:10, 30:20, 30:30, 30:40). The variables measured were sensory and hedonic quality using organoleptic test by 30 semi trained panelists. Data analysis using Kruskal Wallis test and Mann-Whitney test. Determination of the selected formula using the exponential comparison method then analyzed proximate and antioxidant activity. There is a significant difference in sensory quality on the parameters of skin color, filling color, aroma, taste, and mouthfeel, the selected formula based on the organoleptic test is formula 3. The antioxidant activity test result is 12.78 mg/100 g. Water content test 41.45%, ash content test 1.48%, total energy 256,26 Kcal/100 g, protein 5.62%, fat 5.6%, carbohydrates 45.85%. The red bean mochi formulation with a 30:30 ratio was found to have moderate antioxidant activity.